Enhancing web supported learning by adding a management layer to SCORM compliant LMSs - Pinto, Carlos Sousa (2006)
Many Web based learning experiences fail due to bad or absent support. LMSs (Learning Management Systems) must incorporate mechanisms for real time monitorization of the involvement of each participant in a course, allowing the detection of deviations to the scheduled activities, enabling the correction of these deviations [1]. The principal standardization projects in the area do not cover this type of aspects. Those projects are mainly focused on contents and its delivery to the learners participating in the courses [2], [3], [4]. This article describes a proposal of a reference model and functionalities towards a specification of a layer for real time management of user interactions with SCORM (Sharable Content Object Reference Model) compliant LMSs.